Divided We Stand? Coalition Dynamics in the German Union Movement. (26th August 2020) - Behrens, Martin; Pekarek, Andreas
Abstract: Coalitions within national union movements have been an enduring means by which unions pursue shared interests and policy ambitions. Drawing on social movement theory, we focus on the logics shaping union coalitions, and the conditions under which they differ, in order to gain analytical purchase on enduring debates about union behaviour in industrial relations. Taking the German case, we identify four key policy issues that have caused major divisions and competing coalitional activity between unions in the German Trade Union Confederation (DGB) over the period 1964 to 2018. Our analysis suggests that there is a degree of fluidity between instrumental and ideological logics, which relates to the evolving socio‐political contexts that shape the dynamics of union coalitions over time. In the German context, our findings indicate that the relative importance of the logics shaping coalition activity varies with the nature of the threats unions encounter. In the face of more specific and immediate threats, coalitional decision‐making was more likely to be driven by instrumental logic, prioritizing the narrower concerns of the union and its core members. However, where unions' broader social visions came under threat, self‐interest played a more modest role, and choices were more likely to be animated by ideological concerns and questions of public good.